Enhancing Spatial Allocation of Pediatric Medical Facilities for Reduced Travel-Related CO2 Emissions: A Case Study in Tianjin, China - Hongjie Dong; He Zhang; Rui Wang; Yutong Zhang; Yuxue Zhang; Lisha Zhang (Land)
Due to the limited availability of medical facilities and the urgency and irreplaceability of medical-seeking behaviors, the transportation processes used to access these resources inherently result in high carbon emissions. Unfortunately, pediatric medical facilities are among the least substitutable destinations, making it challenging to reduce travel-related CO2 emissions by traditional means such as decreasing travel frequency or optimizing transportation means. This study proposes enhancing the spatial allocation of pediatric medical facilities to effectively reduce travel-related CO2 emissions. This study selects 27 hospitals with pediatric departments in Tianjin as the research subject. It introduces a model for measuring travel-related CO2 emissions for pediatric medical-seeking, STIRPAT, and ridge regression models as well as conducts simulations under various scenarios to test the hypotheses. Therefore, methods for enhancing the spatial allocation of pediatric medical facilities are proposed. The results show that (1) travel-related CO2 emissions for pediatric medical-seeking are the highest in the city center, outpatient-related CO2 emissions surpass inpatient ones, and children’s hospital-related CO2 emissions are higher than those related to comprehensive hospitals, from which potential carbon reduction points can be explored; (2) children’s hospitals with multibranch and composite functional allocations can significantly reduce CO2 emissions; (3) comprehensive hospitals can further alleviate CO2 emissions from children’s hospitals by enhancing the medical level, transportation infrastructure, population distribution, and other spatial environmental factors; (4) from the perspective of low-carbon travel and equity, a spatial allocation strategy should be adopted for children’s hospitals that includes multiple branches and composite functions, while comprehensive hospitals should focus on service capacity, parity, supply–demand ratio, and the population density of children.